2005
DOI: 10.1002/gcc.20266
|View full text |Cite
|
Sign up to set email alerts
|

A role for endogenous reverse transcriptase in tumorigenesis and as a target in differentiating cancer therapy

Abstract: An unexpected result emerging from completion of the genome sequencing project is that a large portion of mammalian genomes is constituted by retrotransposons. A large body of published data supports the conclusion that retrotransposons are biologically active elements and indicates that retrotransposition is an ongoing process in mammalian genomes. Retroelements can act as insertional mutagens altering the coding integrity of genes and, recently, have been found to also affect the expression of cellular genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 76 publications
2
42
0
Order By: Relevance
“…This circumstance suggests that (i) different families of retroelements are not independent entities, but are linked in a functional network, and (ii) such functional network is organized in a hierarchical order, such that a one-way control mechanism flows from L1 to HERV-K expression but does not feedback in the reverse direction. In our previous work, we reported the intrinsic ability of L1 retrotransposons to modulate the expression of protein-encoding genes (Mangiacasale et al, 2003;Sciamanna et al, 2005; reviewed by Sinibaldi-Vallebona et al, 2006). The present results add the novel information that not only the expression of protein-encoding genes, but also that of other retroelement families, are influenced by L1.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This circumstance suggests that (i) different families of retroelements are not independent entities, but are linked in a functional network, and (ii) such functional network is organized in a hierarchical order, such that a one-way control mechanism flows from L1 to HERV-K expression but does not feedback in the reverse direction. In our previous work, we reported the intrinsic ability of L1 retrotransposons to modulate the expression of protein-encoding genes (Mangiacasale et al, 2003;Sciamanna et al, 2005; reviewed by Sinibaldi-Vallebona et al, 2006). The present results add the novel information that not only the expression of protein-encoding genes, but also that of other retroelement families, are influenced by L1.…”
Section: Discussionsupporting
confidence: 65%
“…In line with these views, we have recently shown that LINE-1 (L1)-encoded reverse-transcriptase (RT) plays a key role in early embryonic development Beraldi et al, 2006) and in tumorigenesis (Mangiacasale et al, 2003;Landriscina et al, 2005;Sciamanna et al, 2005; reviewed by Sinibaldi-Vallebona et al, 2006). More specifically, we have found that pharmacological inhibition of endogenous RT using either nevirapine or efavirenz, two non-nucleosidic RT inhibitors widely used in AIDS treatment, reduces cell proliferation and promotes differentiation in human tumorigenic cell lines (Mangiacasale et al, 2003;Landriscina et al, 2005).…”
Section: Introductionmentioning
confidence: 85%
“…I favor the view that the same RT-dependent mechanism operates throughout preimplantation development and in tumor progression, while being inactivated in terminally differentiated cells [for a review see Sinibaldi-Vallebona et al 2006]. The reason why this mechanism is resurrected in tumor cells is unclear, but our preliminary evidence suggest that epigenetic modifications of chromatin architecture affecting genome functions are a major cause.…”
Section: Discussionmentioning
confidence: 85%
“…It has been proposed that retrotransposons modulate the expression of specific genes through a transcriptional interference-based mechanism. To exert such effect on neighboring genes, retrotransposons need not necessarily be full-length, nor retrotransposition-competent, but simply endowed with functional promoter elements [28] . Previous studies have shown that some non-full length L1 elements (even shorter than 500 bp) may yield L1 products such as L1 RNA or active RT [29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…A lot of evidence has indicated that L1 is involved in a wide spectrum of diseases, including cancer [28,33,34] . In colon cancer, the APC gene can be disrupted by somatic insertion of an L1 sequence into the last exon of the gene [35] .…”
Section: Discussionmentioning
confidence: 99%